Dual-track diplomacy: China’s manoeuvre between Japan and the Soviet Union, 1931-1937 - Jin, Z (2024)
This dissertation focuses on China’s diplomatic manoeuvre between Japan and the Soviet Union from 1931 to 1937. It demonstrates that the Nanjing government, led by Chiang Kai-shek, pursued dual-track diplomacy, which aimed at stabilising Sino-Japanese relations through strategic compromises while developing relations with the Soviet Union as a potential ally against Japan. Given the antagonistic relationship between the Soviet Union and Japan, this dual-track diplomacy requires a meticulous strategy. The primary question addressed in this study is how Chiang Kai-shek implemented the dual-track diplomacy. Firstly, the dissertation argues that Chiang Kai-shek took advantage of the factionalism within the Nanjing government, especially the division of responsibilities under the cooperative framework between him and Wang Jingwei. By strategically emphasising and sometimes exaggerating the differences between himself and the diplomatic authorities, as well as adopting policies favourable to the Soviet Union on issues like Xinjiang, Chiang altered Soviet perceptions of his political stance. By 1937, the Soviets had come to view Chiang Kai-shek not as a pro-Japanese leader, as they had in 1933, but as a potential anti-Japanese leader. Secondly, it argues that Chiang Kai-shek adeptly employed secret diplomacy to ensure that Sino-Japanese and Sino-Soviet relations did not adversely affect each other. That involves not only the confidentiality of contacts between the Chinese and the Soviets but also Chiang Kai-shek’s vision towards treaty relationships between the two countries. Through dual-track diplomacy, Chiang Kai-shek postponed the Sino-Japanese War to the greatest extent, allowing time for domestic preparations. Meanwhile, he significantly improved Sino-Soviet relations, thereby securing assistance from the Soviet Union after the war broke out. This diplomatic strategy of balancing among major powers was not only a crucial manifestation of Chiang Kai-shek’s diplomacy but also a legacy adopted by the Chinese communists.